The Effectiveness of a Training Program based on Some Positive Psychology Techniques in Decreasing Learned Helplessness and Developing Psychological Flow among Underachieving University Students - Abdellatif, Mohamed Sayed Mohamed (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the effectiveness of a training program based on some positive psychology techniques in decreasing learned helplessness and developing psychological flow among underachieving university students, also to keep track of the continuing effectiveness of this program after the follow-up period. To this end, the researcher followed the experimental design with one experimental group consisting of 11 university students. The researcher applied the following tools: the training program, the learned helplessness scale (by the researcher), and the psychological flow scale (by Jackson & Marsh 1996). For data analysis and hypotheses validation, the researcher used the "Wilcoxon" test. The findings of the study revealed (a) statistically significant differences between the means of the experimental group ranks in the pre and post-measurements of psychological flow and learned helplessness in favor of the post-measurement and (b) no statistically significant differences between the means of the experimental group ranks in the post and follow-up measurements of psychological flow and learned helplessness (after a month). The research results can benefit stakeholders and staff members in developing psychological flow and reducing learned helplessness among underachieving university students.
Keywords: positive psychology; learned helplessness; psychological flow; underachievement